2018
DOI: 10.3390/pr6110208
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of a Two-Stage Membrane System for Hydrogen Separation in Refining Processes

Abstract: This paper fits into the process system engineering field by addressing the optimization of a two-stage membrane system for H 2 separation in refinery processes. To this end, a nonlinear mathematical programming (NLP) model is developed to simultaneously optimize the size of each membrane stage (membrane area, heat transfer area, and installed power for compressors and vacuum pumps) and operating conditions (flow rates, pressures, temperatures, and compositions) to achieve desired target levels of H 2 product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…12,13,28 Although previous works 13,14 suggested that the two-stage membrane system utilizing a mixed-mode driving force (CP + VP scheme) for CO 2 capture from flue gas (>13 mol % CO 2 in feed) or NG or biogas upgrading (40% CO 2 ) was the best, the feed concentration of the desired product and feed flow rate were much higher than that in this study. Another study by Arias et al 53 reported that the CP + VP scheme in the twostage process shows a cost-optimal process for H 2 separation from refinery processes, with 18 mol % H 2 in the feed. However, they did not include the CP + VP-1 scheme in their investigation, which is shown in our study as an optimal process configuration in a mixed-mode driving force using the two-stage cascade system.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,28 Although previous works 13,14 suggested that the two-stage membrane system utilizing a mixed-mode driving force (CP + VP scheme) for CO 2 capture from flue gas (>13 mol % CO 2 in feed) or NG or biogas upgrading (40% CO 2 ) was the best, the feed concentration of the desired product and feed flow rate were much higher than that in this study. Another study by Arias et al 53 reported that the CP + VP scheme in the twostage process shows a cost-optimal process for H 2 separation from refinery processes, with 18 mol % H 2 in the feed. However, they did not include the CP + VP-1 scheme in their investigation, which is shown in our study as an optimal process configuration in a mixed-mode driving force using the two-stage cascade system.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have thus turned their attention to the membrane separation process, due to its low investment cost and simple operation, to capture CO2 in the coal gasification hydrogen production process. Arias et al [10] proposed a two-stage membrane system for hydrogen separation in refining processes, a H2 product purity of 0.90 and H2 recovery of 90% are achieved. But these literatures have rarely been simultaneously coupled with hydrogen purification [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Arias et al [10] proposed a two-stage membrane system for hydrogen separation in refining processes, a H2 product purity of 0.90 and H2 recovery of 90% are achieved. But these literatures have rarely been simultaneously coupled with hydrogen purification [10][11][12][13][14]. Moreover, Chen et al [15] established a mathematical model for a dual membrane separator, which provided a new way to separate H2/CO2 of shifted syngas.…”
Section: Introductionmentioning
confidence: 99%
“…Since vacuum residue accounts for about half of the crude oil, more attention has been focused on vacuum residue hydroconversion processes, which are capable of converting heavy, inferior petroleum into light, valuable products such as gasoline, jet fuel, and diesel [3,4]. A good process model is important for monitoring the plant-level operation status, optimizing operating conditions, verifying the dynamic adjustment scheme, and maximizing the profit [5][6][7].…”
Section: Introductionmentioning
confidence: 99%